The Effect Referral Barriers to Barriers Delay in Perinatal Mortality in Karawang - Armini, Luh Nik; Susanto, Herman; Hilmanto, Dany (Universitas STRADA Indonesia, 2018)
Perinatal mortality is the biggest contributor to the death of infant mortality. Most of the causes of perinatal mortality can be prevented that the factors of patients, health professionals, referral and availability of health care facilities. Obstacles in the references often found in the delay in recognizing the danger, decision-making by women because it is influenced cultural issues, difficulty gaining access to health services because of problems with the distance. Karawang regency is part of West Java Province perinatal death must be completed. The purpose of this study is the referral process constraints that caused the delay referral perinatal mortality in Karawang. The study design using the sequential explanatory mixed method. Quantitative data were taken through Perinatal Maternal Audit document was tested with Fisher Exact, whereas qualitative research conducted by Focus Group Discussion and interview. The study showed no association with late referral process bottleneck references (p> 0.05 The results of the qualitative research shows that the delay in the referral is more due to the limitations of the tools for referral and indirect costs (meals, round trip hospital costs) causing late picking decision